Victorian fairy tales the revolt of the fairies and elves - Zipes, Jack David (Routledge, 1987)
A collection of fairy tales by Victorian writers, including Lewis Carroll, Charles Dickens, Oscar Wilde, and Rudyard Kipling, with illustrations from the same period.